The sustainable development goals: the contribution of tourism volunteering. Issue 12 (2nd December 2022) - Lockstone-Binney, Leonie; Ong, Faith
Abstract: The tourism workforce is diverse and the literature exploring workforce issues, whilst limited, largely focuses on remunerated workers. There is recognition that volunteering has a significant role to play in achieving the United Nations Sustainable Development Goals (SDGs); however, there is limited literature exploring the role of volunteering relative to the SDGs' architecture. With reference to the tourism workforce, there is also a noticeable lack of studies exploring how tourism volunteering contributes to realisation of the SDGs. In a first, using the lens of critical tourism, this conceptual paper seeks to holistically explore how tourism volunteering can contribute to SDG realisation from the perspectives of host volunteering and (guest) volunteer tourism. This study maps the potential of both forms relative to the volunteering activities that United Nations Volunteers (UNV) has identified as means by which volunteers can support the SDGs. The findings revealed common areas through which host volunteering and volunteer tourism contribute but taken on the whole, volunteer tourism has the greater potential to contribute to the SDGs as a development agenda. Informed by these findings, we develop six propositions to advance recognition and research relating to the contribution of tourism volunteering to the SDGs.